Alternative RNA Splicing Produces Multiple Forms of c-Myb with Unique Transcriptional Activities - O'Rourke, John P. (American Society for Microbiology (ASM), 2008)
The c-Myb transcription factor regulates the proliferation and differentiation of hematopoietic cells, and activated alleles of c-myb induce leukemias and lymphomas in animals. Relatively minor changes in the structure of c-Myb protein change the genes that it regulates and can unleash its latent transforming activities. Here, quantitative assays were used to analyze the alternative splicing of human c-myb transcripts. We identified an array of variant transcripts, expressed in highly regulated, lineage-specific patterns, that were formed through the use of alternate exons 8A, 9A, 9B, 10A, 13A, and 14A. Expression levels of the different splice variant transcripts were regulated independently of one another during human hematopoietic cell differentiation, and the alternative splicing of c-myb mRNAs was increased in primary leukemia samples. The alternatively spliced c-myb transcripts were associated with polysomes and encoded a series of c-Myb proteins with identical DNA binding domains but unique C-terminal domains. In several types of assays, the variant c-Myb proteins exhibited quantitative and qualitative differences in transcriptional activities and specificities. The results suggest that the human c-myb gene encodes a family of related proteins with different transcriptional activities. Enhanced alternative splicing may be a mechanism for unmasking the transforming activity of c-myb in human leukemias.